Analysis of the Application of Logical Operations to Cryptographic Transformations of Information Security Means - Madaminov, M. M.; Farhodjonov, A. F. (Jurnal Pendidikan Matematika, 2024)
In the article, the solution to the problem of determining logical operations that ensure cryptographic stability of the transformation of algorithms of cryptographic methods of information security is justified by the criterion of regularity - equal distribution"0" and "1" in the truth table. A logical operation with a truth table of uniform distribution of "0" and "1" and or blocks of bits has the property of cryptographic resistance.